ANALISIS PROSES PELAKSANAAN AKAD QARDH WAL IJARAH PADA PRODUK TALANGAN UMROH KASUS DI BANK SYARIAH MANDIRI KANTOR CABANG BOGOR - Fadly, Fadly; Nawawi, Kholil; Arif, Suyud (EDUTECH CONSULTANT, 2019)
This study uses a qualitative descriptive approach, which is research that seeks to describe the symptoms, events, and events that are happening now. Descriptive research focuses attention on the actual problem, as it was at the time the research took place. Data collected in the form of words, images and not numbers. There are several steps undertaken to finance the Umrah bailout fund regarding the process that must be passed by prospective users of the Umrah bailout product, including the following: prospective customers must become official customers of Bank Syariah Mandiri, customers come directly to the Bank Syariah Mandiri office by bringing file, then to the financing section and there the financing section will conduct a survey, after it has been decided that the right to receive financing will then carry out a mutually agreed agreement, open a savings account with a minimum balance of Rp.200,000 per person, the customer must have collateral. Legal analysis on the implementation of the umroh bailout product process at Bank Syariah Mandiri uses a sharia-compliant agreement. Of course, Bank Syariah Mandiri already has a sharia supervisory board and a national sharia council, they certainly do not carelessly create a system on their products. If it is reviewed in the feasibility of this product user, Bank Syariah Mandiri does not arbitrarily provide its products, so it is not someone who is truly unable to pay off, but Bank Syariah Mandiri will provide this umroh bailout product to people who can afford to pay in installments.